The Factors Influencing Dividend Payout Rates of Listed Companies in the Stock Exchange of Thailand in the Market for Alternative Investment (MAI) Group - วงค์เสือ กัญญาวีร์; บุญยสาร ฐนิดา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study the factors that influence the dividend payout rate of listed companies in the Stock Exchange of Thailand in the Market for Alternative Investment (MAI) group, including profitability, liquidity ratio, debt repayment ability, book value, sales growth, and business size, in order to serve as a guideline for those interested in investment returns in the form of dividend payout rates. The sample group used in the study was 103 companies listed on the Stock Exchange of Thailand (SET) in the Market for Alternative Investment (MAI). Secondary data was collected from annual reports and Form 56-1 from 2020 to 2024. Data were analyzed using descriptive statistics, including mean, maximum, minimum, standard deviation, and inferential statistics to test hypotheses, including Pearson’s correlation coefficient analysis and multiple regression analysis at a statistical significance level of 0.05. The results of a study of factors influencing dividend payment rates of companies listed on the Stock Exchange of Thailand: in the group of MAI stock exchanges (MAI), a multi-regression analysis found that the profitability ability to pay debts And the market value to book value influences the dividend payout ratio. at a significant level of 0.05. sales expansion and size of business It has no influence on the dividend payout ratio.